Analysis of cohesion and altruism among organization members: the case of Tanoh Rincong student association - Mohammed, Adam Andani; Uddin, Md Sayed; Saad, Nurulwahida; Eid, Iyad M.Y. (Macrothink Institute, 2016)
This paper examined the influence of group dynamics in terms of cohesion and altruism on members of Tanoh Rincong Student Association (TARSA). This was with the view to determining how these two interpersonal relationship dimensions contribute to the social effectiveness and collaboration of members in this association of Indonesia students in the International Islamic University Malaysia. The study adopted survey research design. The instrument utilized for this study was a structured 18- item questionnaire. The Spearman’s rho correlation and Mann-Whitney statistical methods were utilized to determine the relationship between cohesion and altruism as well as the difference of those dimensions in terms of the participants’ role and position in the organization. The findings of the study revealed that there was a moderately positive relationship between cohesion and altruism among the TARSA members (p = >0.05). A significant difference of cohesion score was not found between TARSA committee and TARSA members (p = >0.05). However, there was a significant difference in altruism scores between the two member groups (p = <0.05). Though a significant relationship between the two dimensions was not found, item analysis indicated a high level of commitment among the members towards the cause of TARSA and a high sense of brotherhood and compassion for each other. This study may therefore conclude that cohesion and altruism are factors that help foster a positive attitude and collective action that could promote cordial interpersonal relations and thus the success of the organization.